Implementasi Dana Desa di Kecamatan Gantarang Kabupaten Bulukumba - Andi Fitrah Rezkyah Ramadhani Fachrin (Departemen Ilmu Pemerintahan Fisip Unhas, 2023)
Village Funds are one of the Indonesian government's policy instruments aimed at accelerating rural development, improving the quality of public services, and promoting community empowerment toward self-reliant and prosperous villages. The success of Village Fund implementation largely depends on the ability of village governments to plan, implement, and utilize the allocated budget effectively in accordance with community needs. This study aims to analyze the implementation of Village Funds in Gantarang District, Bulukumba Regency, focusing on village fund planning and utilization, village development implementation, and community empowerment. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and literature review. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Village Funds in Gantarang District has generally been carried out effectively. In terms of planning and utilization, village governments involved community members through village deliberation forums in determining development priorities. Regarding village development, Village Funds were utilized to construct and improve infrastructure and public facilities that support community activities and enhance public services. In terms of community empowerment, Village Funds were used to support various programs aimed at improving community skills and capacities. the implementation of Village Funds has contributed positively to rural development and community welfare improvement, although further optimization is needed to ensure more sustainable outcome.